DEMON AS FORM OF SATIRICAL STATEMENT IN DRAMA THE TRAGICAL HISTORY OF DOCTOR FAUSTUS - Maulani Fitri Fadlilah; Pepen Priyawan (CALL, 2021)
This study focuses on a word or line that is identified as satire in a drama entitled The Tragical History of Doctor Faustus. The data was taken in the form of dialogues from the characters. Demon as a satirical expression means that the words or line identified as satire was built by several elements that are attached with demon characteristics (demonic). Demon is a creature who has clear characteristics as a bad set. The bad character of the demon is representative of satire. The character demon is a representation of ugliness or evil of the object criticized in the drama The Tragical History of Doctor Faustus. Researchers used the descriptive analysis method by Ratna (2004) in conducting this research. Descriptive analysis is a method used to analyze data and facts in the text and then interpret them. The researcher used two theories in seeing the story. Inter-relationship principle and semiotic.   The results of this research found three important elements in accordance with the topic of this research. The first is the antagonist character Mephistophilis, the demon. The second is the allusion to Franciscan Friar. Third, the phrase holy shape becomes the devil best is satire. Thus, the combination of elements leads to a demon as a form of satirical expression.Keywords: Satire, Demon, Allusion